2012
DOI: 10.1007/s11356-012-1004-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing line intercept sampling and estimation for feral swine damage levels in ecologically sensitive wetland plant communities

Abstract: Ecological sampling can be labor intensive, and logistically impractical in certain environments. We optimize line intercept sampling and compare estimation methods for assessing feral swine damage within fragile wetland ecosystems in Florida. Sensitive wetland sites, and the swine damage within them, were mapped using GPS technology. Evenly spaced parallel transect lines were simulated across a digital map of each site. The length of each transect and total swine damage under each transect were measured and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Engeman et al (2003Engeman et al ( , 2004aEngeman et al ( , 2007c found that sampling the amount of swine rooting over time through line-intercept or plots was a cost-and labor-efficient method for estimating the extent of rooting damage and relating it to changes in swine population size in various Florida natural areas. Thomas et al (2013) optimized the application of lineintercept sampling design and estimation procedures for assessing swine damage in light of the practical considerations typical of ecological sampling. In a more spatially explicit manner, Chavarria et al (2007) used hand-held GPS units to map and estimate damage areas of "simple polygons," which were also sampled from the greater survey area using line-transects.…”
Section: Discussionmentioning
confidence: 99%
“…Engeman et al (2003Engeman et al ( , 2004aEngeman et al ( , 2007c found that sampling the amount of swine rooting over time through line-intercept or plots was a cost-and labor-efficient method for estimating the extent of rooting damage and relating it to changes in swine population size in various Florida natural areas. Thomas et al (2013) optimized the application of lineintercept sampling design and estimation procedures for assessing swine damage in light of the practical considerations typical of ecological sampling. In a more spatially explicit manner, Chavarria et al (2007) used hand-held GPS units to map and estimate damage areas of "simple polygons," which were also sampled from the greater survey area using line-transects.…”
Section: Discussionmentioning
confidence: 99%
“…As identified in recent sampling research (Thomas et al 2013), estimation of the proportion of each steephead's valley floor with damage was accomplished by first summing the total area of all strip transects within the steephead. The total area across all transects that 1 3 was under water in the steephead stream was subtracted from this total to define the total area of terrestrial steephead valley floor habitat sampled.…”
Section: Damage Estimationmentioning
confidence: 99%
“…There are also methods now available that are not as ''fieldintensive'' that can provide high-quality estimates of damage within a site (Thomas et al 2013). However, to monitor a substantial number of sites over time as we have done requires human resources that are unlikely to be available in many damage assessment circumstances.…”
Section: Quantifying Damagementioning
confidence: 99%